KEANEKARAGAMAN ARTHROPODA PADA TANAMAN BAWANG MERAH Allium ascalonicumL. PADA POLA TANAM YANG BERBEDA - Sukarmin, Sukarmin; Nasir, Burhanuddin; Wahid, Abd (AGROTEKBIS, 2018)
Red onion (Allium azscalonicum L.) is a kind of Horticultural commodity that has big opportunity in the sector of Agribusiness. This research aimed to determine of the diversity and evenness of Arthropod that are distributed under different planting patterns. This research started on April until July 2016, located in Sidera, Sigi Biromaru Sub district, Sigi Biromaru Regency, Central Sulawesi. The method used in this research was an absolute method (a unit sample used was an area size of 1m x 4m within which observations to all individual Arthropod were done systematically) and the nisbi method (Pitfall, Sweep, and Yellowtraps were used). The planting pattern simple mented in this research were red onion â red onion, red onion â chili, and red in the planting pattern of red onion â beans. The diversity of Arthropod on the different planting patterns and the planting pattern of red onion â chili and red onion â beans was classified as medium category with the production of red onion was 3.49 ton/ha.Â Keywords : Arthropoda, Diversity, Onion, Planting Patterns.